Implementation of Preference Selection Index Method in Decision Support System for Selecting School Inventory Users - Doris Yolanda Saragih; Kalvin Sinaga (Journal of Computer Networks, Architecture and High Performance Computing, 2020)
This study aims to solve the problem of using a limited inventory of supporting media for learning at SD 096782 Tumorang Huta Dua Tumorang school, Gunung Maligas District, Simalungun Regency. The limitations of school inventories in the use of instructional media must be distributed to teachers so that they can be used in teaching. Therefore, the difficulty of distributing school inventory was overcome by implementing a decision support system using the Preference Selection Index (PSI) method. This method uses 6 criteria consisting of: years of service, behavior, performance, attendance, responsibility, and last education. The results of the application of the DSS with the PSI method obtained alternatives that are priority recommendations for school inventory users. The recommendation results obtained from the application of the DSS with the PSI method are Teacher_3 alternative with a final value of 0.8506. The second alternative is Teacher_01 with a final score of 0.8190 and the third alternative is Teacher_07 with a final score of 0.7846.